A new family of standardized and symmetric indices for measuring the intensity and importance of plant neighbour effects. Issue 5 (3rd January 2017) - Díaz‐Sierra, Rubén; Verwijmeren, Mart; Rietkerk, Max; de Dios, Víctor Resco; Baudena, Mara
Summary: Measurements of competition and facilitation between plants often rely upon intensity and importance indices that quantify the net effect of neighbours on the performance of a target plant. A systematic analysis of the mathematical behaviour of the indices is lacking and leads to structural pitfalls, e.g. statistical problems detected in importance indices. We summarize and analyse the mathematical properties that the indices should display. We review the properties of the commonly used indices focusing on standardization and symmetry, which are necessary to avoid compromising data interpretation. We introduce a new family of indices 'Neighbour‐effect Indices' that meet all the proposed properties. Considering the commonly used indices, none of the importance indices are standardized, and only RII (Relative Interaction Index) displays all the required mathematical properties. The existing indices show two types of symmetries, namely, additive or commutative, which are currently confounded, potentially resulting in misleading interpretations. Our Neighbour‐effect Indices encompass two intensity and two importance indices that are standardized and have different and defined symmetries. Our new additive intensity index, NIntA, is the first of its kind, and it is generally more suitable for assessing competition and facilitation intensity than the widely used RII, which may underestimate facilitation. Our new standardized importance indices solve the main statistical problems that are known to affect C imp and I imp . Intensity and importance with the same symmetry should be used within the same study. The Neighbour‐effect Indices, sharing the same formulation, will allow for unbiased comparisons between intensity and importance, and between types of symmetry.